Social protection in Asia and the Pacific: Inventory of non-contributory programmes - International Policy Centre for Inclusive Growth (IPC-IG); United Nations Children's Fund (UNICEF) (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
Social protection programmes are now widely recognised as key policy instruments for developing countries to combat poverty. The 2030 Agenda for Sustainable Development has explicitly recognised the importance of implementing "nationally appropriate social protection systems and measures for all, including floors" as an explicit target under Sustainable Development Goal 1: "End poverty in all its forms everywhere". Nonetheless, knowledge of specific programmes being implemented across developing countries can be fragmented or inaccessible. This study intends to contribute towards addressing these gaps, providing an overview of non-contributory social protection programmes in selected regions in Asia and the Pacific. Moreover, the profiles presented will also be made available online, through the socialprotection.org platform.
Keywords: 330; Social protection; Asia; Pacific; inventory; non-contributory programmes